Synaptic element for neuromorphic computing using a magnetic domain wall device with synthetic pinning sites - Jin, Tianli (2020)
The ability to make devices that mimic the human brain has been a subject of great interest in scientific research in recent years. Current artificial intelligence algorithms are primarily executed on the von Neumann hardware. This causes a bottleneck in processing speeds and is not energy efficient. In this work, we have demonstrated a synaptic element based on a magnetic domain wall device. The domain wall motion was controlled with the use of synthetic pinning sites, which were introduced by boron (B+) ion-implantation for local modification of the magnetic properties. The magnetization switching process of a Co/Pd multilayer structure with perpendicular magnetic anisotropy was observed by using MagVision Kerr microscopy system. The B+ implantation depth was controlled by varying the thickness of a Ta overcoat layer. The Kerr microscopy results correlate with the electrical measurements of the wire which show multiple resistive states. The control of the domain wall motion with the synthetic pinning sites is demonstrated to be a reliable technique for neuromorphic applications.